Van Gogh : the life - Naifeh, Steven, (Steven W.), 1952-; Smith, Gregory White (New York : Random House, 2011)
Draws on newly available primary sources to present an in-depth, accessible profile that offers revisionist assessments of the influential artist's turbulent life and genius works.
Includes bibliographical references (pages [895]-918) and index.
Keywords: Gogh, Vincent van, -- 1853-1890; Gogh, Vincent van, -- 1853-1890 -- Psychology; Gogh, Vincent van, -- 1853-1890; Gogh, Vincent van, -- 1853-1890 -- Psychology; Artists -- Netherlands -- Biography; Artists -- Netherlands -- Biography